Combining real-time fluorescence spectroscopy and flow cytometry to reveal new insights in DOC and cell characterization of drinking water - Schuster, Jonas; Huber, Johanna; Stumme, Jakob; Grieb, Anissa; Ernst, Mathias (Frontiers in Environmental Chemistry, 2022)
Sudden changes in drinking water quality can cause harmful consequences for end users. Thus, real-time monitoring of drinking water quality can allow early warning and provide crucial gains for securing safe water distribution. This study investigated the advantages of simultaneous real-time measuring of flow cytometry and fluorescence spectroscopy. A contamination event was investigated in a laboratory-scale analysis by spiking drinking water samples with organic nutrients. Flow cytometric data were analyzed by creating fingerprints based on differentiation into high and low nucleic acid cells (HNA/LNA). The detailed characterization of these data showed that an increase in HNA cells indicated an increase in the bacterial growth potential even before actual TCC increases. The fluorescence data was decomposed via the PARAFAC method to reveal seven fluorescent components. Three aromatic protein-like components were associated with the microbiological condition of the drinking water cells; namely, Components 4 (λEx = 279 nm, λEm = 351 nm), 6 (λEx = 279 nm, λEm = 332 nm), and 7 (λEx = 276 nm, λEm = 302 nm). Component 6 was identified as a possible organic variable for appropriate monitoring of TCC, whereas Components 4 and 7 were identified as organic compounds representing nutrients for organisms present in drinking water. Overall, combining both methods for real-time monitoring can be a powerful tool to guarantee drinking water quality.